2004
DOI: 10.1093/ndt/gfg604
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between gene polymorphisms of nitric oxide synthase and renin-angiotensin system in the progression of membranous glomerulonephritis

Abstract: This study is the first to demonstrate a role for an interaction between simultaneous variations of genes encoding for NOS and components of RAS in the progression of MGN. Interactions between various polymorphisms may explain conflicting results obtained in previous studies that examined single gene variations, since the effect of a single locus variation may be influenced by the simultaneous presence of other variant alleles in polygenic diseases such as primary GN. However, the small sample sizes and possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Prior studies related the incidence of MGN and several gene polymorphisms: TNF-a gene G-308A, ACE insertion or deletion (ACE I/D), angiotensin II Type 1 receptor (AT1R 1166A/C), angiotensinogen (AGT M235T), and NOS (ecNOS4b/a). [21][22][23] This study focused on IL-6 C-572G (rs1800796) SNP previously investigated for abdominal aortic aneurysms (AAAs) and coronary heart disease. 24,25 We found strong correlation between MGN and IL-6 C-572G SNP: C allele and CC genotype frequency at IL-6 C-572G SNP was definitely higher in MGN patients.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies related the incidence of MGN and several gene polymorphisms: TNF-a gene G-308A, ACE insertion or deletion (ACE I/D), angiotensin II Type 1 receptor (AT1R 1166A/C), angiotensinogen (AGT M235T), and NOS (ecNOS4b/a). [21][22][23] This study focused on IL-6 C-572G (rs1800796) SNP previously investigated for abdominal aortic aneurysms (AAAs) and coronary heart disease. 24,25 We found strong correlation between MGN and IL-6 C-572G SNP: C allele and CC genotype frequency at IL-6 C-572G SNP was definitely higher in MGN patients.…”
Section: Discussionmentioning
confidence: 99%
“…A 27-bp long repeat in the fourth intron of endothelial NOS (eNOS) designated as the 4a/4b polymorphism has been reported that in the presence of ACE I/D or M235T polymorphism increased the risk of renal disease progression (52).…”
Section: Interaction Of Ace I/d Polymorphism With Enos Gene Polymorphismmentioning
confidence: 99%
“…Again, results of genetic studies were contrasting, with some authors showing an association with the progression of IgA nephropathy (89) that was not confirmed by others (90). Of note, however, in a combined gene analysis of eNOS 4a/4b, ACE I/D, AGT M235T, and AT1R A166C polymorphisms in a large cohort of patients with idiopathic membranous nephropathy, Stratta et al found that the combination of aaϩba of eNOS 4a/4b genotypes with IIϩID ACE I/D or TTϩMT AGT M235T genotypes was associated with accelerated renal disease progression, whereas the same eNOS polymorphism had no predictive role when considered alone (91). This finding suggests that in some circumstances a single gene variant may result in appreciable phenotypic changes only upon combination with other polymorphisms that may result in additional or synergistic effects on the same metabolic pathways.…”
Section: Other Non-ras Polymorphisms and Their Interactions With The mentioning
confidence: 99%